Strategies for Enhancing Islamic Education Teachers’ Competencies Through the Utilization of Smart Boards - Febrita Febrita; Mu’amar Aziz; Rahmat Hidayat; Jamilus Harun (EDUJAVARE: International Journal of Educational Research, 2026)
The development of educational technology in the digital era has a great influence on the implementation of learning in educational institutions. This study aims to find out the strategy to improve the competence of Islamic Religious Education teachers through the use of Smart Boards at MAN 1 Solok. The focus of the research includes planning, implementing, and evaluating the use of Smart Boards in improving teacher competence. The research uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation. The research informants consisted of the head of the madrasah, the deputy head of the madrasah for curriculum, the Islamic Religious Education teacher, and the school operator. The results of the study show that planning to improve teacher competence is carried out through the preparation of training programs, the provision of technological facilities, the formation of a companion team, and the preparation of a schedule for the use of Smart Boards. The implementation of improving teacher competence is carried out through training on the use of Smart Boards, technology-based learning assistance, the application of interactive media in the learning process, and the development of teachers' creativity in compiling digital materials. Evaluation is carried out through learning supervision, assessment of teachers' ability to operate Smart Boards, evaluation of student learning outcomes, and program follow-up meetings. The use of Smart Boards has a positive impact on improving the pedagogical, professional, social, and personality competencies of Islamic Religious Education teachers at MAN 1 Solok.